2012
DOI: 10.1021/ac3031465
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Mid-Infrared Cavity Enhanced Absorption Spectrometer for Breath Acetone Detection

Abstract: A high-resolution absorption spectrum of gaseous acetone near 8.2 μm has been taken using both Fourier transform and quantum cascade laser (QCL)-based infrared spectrometers. Absolute absorption cross sections within the 1215-1222 cm(-1) range have been determined, and the spectral window around 1216.5 cm(-1) (σ = 3.4 × 10(-19) cm(2) molecule(-1)) has been chosen for monitoring trace acetone in exhaled breath. Acetone at sub parts-per-million (ppm) levels has been measured in a breath sample with a precision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Furthermore, also broadband absorbing molecules, such as acetone [152], can be detected in breath samples with a portable and compact system. For example, Hancock et al have demonstrated lab-based mid-and near-IR CEAS systems for breath acetone detection [98,101]. Most recently, the same group have reported on a portable and compact device for measuring acetone in breath samples; the device features a 7 cm long high-finesse optical cavity that is coupled to a miniature adsorption pre-concentrator containing 0.5 g of polymer material [102].…”
Section: Opportunitiesmentioning
confidence: 99%
“…Furthermore, also broadband absorbing molecules, such as acetone [152], can be detected in breath samples with a portable and compact system. For example, Hancock et al have demonstrated lab-based mid-and near-IR CEAS systems for breath acetone detection [98,101]. Most recently, the same group have reported on a portable and compact device for measuring acetone in breath samples; the device features a 7 cm long high-finesse optical cavity that is coupled to a miniature adsorption pre-concentrator containing 0.5 g of polymer material [102].…”
Section: Opportunitiesmentioning
confidence: 99%
“…Figure 3 shows a simulated absorption profile of 500 ppbv acetone and 200 ppbv ethanol in the region of 1150-1300 cm´1 for a path length of 1 km at a pressure of 1 atm. The inset in the top right corner shows the region of 1216.5 cm´1 and 1220 cm´1 that was proposed for breath acetone analysis earlier [18]. Although this wavelength region was chosen because of the minimal spectroscopic interference from water and CO 2 , the contribution of ethanol results in an elevated absorption line without any significant lineshape change.…”
Section: Calibration and Detection Limitmentioning
confidence: 99%
“…Overall, external cavity quantum cascade lasers (EC-QCLs) [13][14][15] represents a light source with high power, broad tuning range, narrow linewidth, and rapid wavelength tuning for the sensitive and accurate detection of trace gases like in breath analysis [16,17]. Examples of applications using EC-QCLs in narrowband absorption include detection of exhaled acetone [18,19], ammonia [20] and nitric oxide [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to the experiment performed, the matrix factor value obtained for the QCL was 101.376%, meaning that at this concentration, there was ions enhancement, although not significantly, the value was near 100% [10][11][12][13]. The matrix factor value obtained in the high concentration was 85.053%, meaning that there was ions suppression [14,15].…”
Section: Selectivity Testmentioning
confidence: 95%